RFID Antenna Near-field Characterization Using a New 3D Magnetic Field Probe - Kassem Jomaa; Fabien Ndagijimana; Hussam Ayad; Majida Fadlallah; Jalal Jomaah (Advances in Science, Technology and Engineering Systems Journal, 2017)
In this paper the design of a new 3D magnetic field (H-field) probe with a near-field scanning system is presented, then the near electromagnetic fields radiated by a Library RFID system is characterized. The proposed system is developed in order to determine the magnetic near-field emitted by electronic devices. The designed isotropic H-field probe consists of three orthogonal and identical loops each of diameter of 6 mm having 3 turns. The antenna factor of the designed probe is presented for a frequency range from 10 MHz to 1 GHz. The designed probe is tested and validated using a standard passive circuit as a device under test. An RFID reader antenna is also designed and simulated on HFSS (high frequency structural simulator) and the radiated magnetic field, obtained by simulations, is then compared to the real measured one above the fabricated circuit. The obtained levels are checked if they satisfy the European and ICNIRP Electromagnetic Fields Guidelines.
Keywords: Near-field Measurements; Magnetic-field Probe; Exposure; Electromagnetic fields; RFID